Analisis Kesalahan Mahasiswa Dalam Menyelesaikan Soal Pembuktian Teorema Binomial Pada Sifat Simetrik - Mukhlis, Akhmad; Ulum, Darul; Utami, Yudy Tri (AS-SUNNIYYAH, 2024)
This research was conducted to observe students' error in working on problems proving the binomial theorem on the symmetric properties of binomial coefficients. This type of research is qualitative research. This research uses a test method, namely by working on questions followed by interviews. This research involved students from the Tadris Mathematics Study Program at Al Falah As Sunniyah Kencong Jember University in the second semester of the 2023/2024 academic year with a total of 17 students. The 17 students were grouped into 3 cognitive abilities, namely high, medium and low cognitive. The subjects of this research consisted of three students with each student representing each cognitive ability group. The results of the research show that the types of language interpretation errors are made by subjects with high and moderate cognitive abilities, namely not writing the correct sentences when drawing conclusions. Conceptual errors were made by subjects with medium and low cognitive abilities in the form of errors in the proof steps. Procedural errors were made by subjects with moderate and low cognitive abilities, namely not having carried out complete calculations when applying the theorem in numerical form. Technical errors were made by subjects with low cognitive abilities, namely writing the same steps repeatedly. Errors in drawing conclusions were made by subjects with high, medium and low cognitive abilities. The three subjects considered the verification process to be complete. All errors are caused by a lack of understanding of the concept, carelessness in the proof process and not being careful in reading the questions.